Juridical Analysis of Law Enforcement Against Terminals for Self-Interest (TUKS) in Tanjung Pinang City - Harry Priambodo; Parameshwara Parameshwara; Ramlan Ramlan; Soerya Respationo; Erniyanti Erniyanti (International Journal of Social Welfare and Family Law, 2024)
Law enforcement against the Self-Interest Terminal (TUKS) in Tanjung Pinang City is an important issue in the context of shipping safety and environmental protection. The background of this research is based on various violations that occur in the field, such as lack of facility maintenance, non-fulfillment of safety standards, and environmental pollution, which shows the absence of suboptimal law enforcement by the Tanjung Pinang Class II Port Authority (KSOP). The purpose of this study is to assist the legal arrangements that regulate TUKS, identify obstacles in law enforcement, and provide suggestions to overcome these obstacles to improve the effectiveness of law enforcement. The research method used is a normative juridical approach with an analysis of applicable laws and regulations, including Law No. 17 of 2008 concerning Shipping, Law No. 32 of 2014 concerning Marine Affairs, and Regulation of the Minister of Transportation Number PM 51 of 2011. In addition, an empirical juridical approach is carried out by interviews and observations to obtain empirical data on the application of law enforcement. The results of the study show that law enforcement by KSOP Class II Tanjung Pinang faces several significant obstacles, such as limited human resources and facilities, lack of coordination between agencies, complicated bureaucratic related procedures, and low awareness and compliance of companies with applicable regulations. These obstacles result in the supervision and enforcement of violations in TUKS not running effectively. To overcome these obstacles, this study suggests several strategic steps. First, increase the capacity and resources of KSOP by increasing protected labor and providing modern equipment. Second, strengthen coordination between agencies through the formation of special forums or committees and the implementation of bureaucratic procedures to accelerate the handling of violations. Third, increasing the awareness and presence of the company through socialization and education programs and involving the public in reporting violations. For this reason, it is recommended to increase the allocation of resources, strengthen coordination between related agencies through the formation of forums or special committees, the community, especially companies that operate TUKS, must actively participate in socialization and education programs organized by KSOP Class II Tanjungpinang and the government and for the Civil Servant Investigator Position to be included in the Position Map within the Technical Implementation Unit of the Directorate General of Sea Transportation of the Ministry Transportation at KSOP Class II Tanjungpnang.